Health and social care integration: Insights from international implementation cases - Matos, R. C. de.; Nascimento, G.; Fernandes, A. C.; Matos, C. (Journal of Market Access & Health Policy, 2025)
The integration of health and social care is increasingly recognized as essential to address population ageing, the rise in chronic diseases, and persistent health inequities. Across Europe, diverse models have been developed to improve service coordination, resource efficiency, and person-centered care. This paper aims to explore international experiences in integrating health and social care, identify common strategies and challenges, and provide insights to inform policy development in countries where integration remains incipient, with a focus on Portugal. A qualitative comparative approach was employed. A systematic literature review was conducted across PUBMED, MEDLINE, and Google Scholar, including peer-reviewed articles, policy reports, and government documents. Thematic analysis was used to identify integration models, enablers, and barriers across different countries. Different models reveal that joint governance, pooled funding, strong community involvement, and digital innovation are key enablers of integration. However, common challenges persist, including fragmented governance, inconsistent implementation, and financial sustainability. In Portugal, structural separation between the health and social sectors continues to limit strategic alignment. Successful integration depends on political commitment, shared vision, and active stakeholder collaboration. European models offer adaptable lessons for Portugal and similar systems, especially regarding intersectoral coordination and preventive care. Integrating health and social care is vital for building resilient, equitable systems. Portugal must adopt a cohesive national strategy; strengthen local implementation; and embrace person-centered, sustainable solutions to ensure long-term impact. Integrating the health and social sectors is indispensable in navigating the ever-evolving healthcare landscape and promoting holistic well-being.